지방정부의 통일교육 법제 정비를 위한 일고찰 - 차승주(Cha Seung Joo) (통일교육연구, 2020)
일상의 공간인 지역 사회에서 진행되는 지방정부 차원의 통일교육은 중앙정부 주도의 기존 통일교육을 보완할 수 있을 것으로 기대한다. 이에 본 논문에서는 17개의 광역 지방자치단체와 교육자치단체를 중심으로 지방정부의 통일교육 관련 법령 현황을 전반적으로 살펴보고, 지방정부 통일교육을 내실 있게 실시하기 위한 방안과 과제를 법·제도적 측면에서 고찰했다. 2020년 9월 현재, 17개 광역 시·도에는 대부분 교육청 또는 지방정부가 제정한 통일교육 관련 조례가 존재하는데, 그 형식과 내용 등의 면에서 지역별로 큰 차이를 보이지는 않는다. 그러나 통일교육의 지속성과 일관성의 확보 문제와 함께 통일교육에 대한 관심과 의지, 여건 조성 등에 있어서 지역별로 존재하는 격차는 지방정부의 통일교육이 안고 있는 한계이자 과제다. 또한 지역적 특색을 반영한 지방정부 차원의 특수성과 중앙정부 차원의 보편성을 어떻게 조화롭게 추구해야 할 것인가에 대한 관심과 고민이 부족한 점도 한계로 지적할 수 있다. 교육의 수준과 비중, 인프라의 질적 차이 등으로 인한 지역별 교육격차도 문제로 제기될 수 있다. 따라서 지방정부 차원에서 교육 접근성을 높이고, 지역 특색을 반영한 통일교육 내용과 방법을 개발하려는 노력이 필요하다. 또한 통일교육에 대한 책임과 역할, 보상을 확실하게 규정하여 지역사회 내의 학교 통일교육을 실질적으로 강화하는 것도 중요하다. 마지막으로, 지방정부의 통일교육은 분단으로 인한 지역사회 내의 상처를 치유하고 갈등을 해결하여 화해를 이루어내는 역할을 수행해야 한다. In this paper, the current state of local government' s unification education related laws and regulations were examined in general, focusing on 17 metropolitan local governme nts and educational municipalities, and the measures and tasks for implementing local government unification education in a substantial manner were examined in terms of law and system. There are most ordinances related to unification education enacted by the education office or local government in 17 metropolitan cities and provinces, and there is no big difference in terms of form and contents. However, the gap in regional areas in terms of the issue of securing continuity and consistency of unification education, interest in unification education, willingness to create conditions, etc. is a limit and task of the local government' s unification education. In addition, the lack of interest and concern about how to pursue the local government-level specificity reflecting regional characteristics and the universality of the central government-level can be pointed out as a limit. The regional educational gap due to the level and proportion of education and the quality difference of infrastructure can be raised as a problem. Therefore, it is necessary to make efforts to improve the accessibility of education at the local government level and to develop the contents and methods of unification education reflecting local characteristics. It is also important to strengthen the school unification education in the community by clearly defining the responsibility, role and compensation for unification education. Finally, the unification education of local government should play a role of healing the wounds in the community due to division and solving conflicts to achieve reconciliation. KCI Citation Count: 5